PERENCANAAN KOMUNIKASI DINAS KOMUNIKASI, INFORMATIKA, STATISTIK DAN PERSANDIAN KOTA PEKANBARU DALAM MENSOSIALISASIKAN PROGRAM SMART CITY - Annisa Citra Triyandra; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Pekanbaru city has increased population, that is resulting in declining public facilities, so peoples want to livable city. To realize the peoples desire, Government of pekanbaru city are launched smart city program. In one year of launched the smart city program, there are still many peoples who dont know about smart City program in Pekanbaru, so Diskominfo need to socialize the smart city program. In socializing smart city program, diskominfo conduct a communication planning. The purpose of this research is to describe and analyze communication program of the Communications, Information Technology, Statistics and Coding of Pekanbaru City In socializing smart city program.This research uses qualitative descriptive methods, with the subject of research are Head of E-Government Organizer and Staff of Communication, Informatics, Statistic and Coding of Pekanbaru City which is involved in socialization plan of smart city program. Data collected through interviews, observation, and documentations. To test the validity of the data the author uses an extension of participation and triangulation.The results of this research is the meaning of communication planning Diskominfo Pekanbaru city in analyzing the target communications categorized into general goals and special targets, in terms of message design Diskominfo Pekanbaru City convey messages in the form of information and persuasive, in terms of media selection Diskominfo Pekanbaru city using print media and Electronic media, in terms of determination of destination Diskominfo Pekanbaru City run the vision and mission that has been made so that later all layers in the Pekanbaru understand smart city program, and in terms of evaluation smart city program Diskominfo Pekanbaru city has not been maximized.Key Word : Communication Planning, Socialization, Smart City